Fibula Nail Outcomes in Soft Tissue Compromised Ankle Fractures. (May 2022) - Ahmed, Maryam; Barrie, Andrew; Kozhikunnath, Arun; Thimmegowda, Abilash; Ho, Sebastian; Kunasingam, Kumar; Guryel, Enis
Background: To determine the clinical outcomes following fibula nail fixation and to identify the indication for the use of fibula nails in lower limb fractures. Methods: Retrospective study of adult patients from 2 major trauma centers (MTCs) and 9 trauma units (TUs) who underwent fibula nail fixation for AO/OTA 44 fractures between January 1, 2018, and October 31, 2020. Outcome measures included infection, metalwork complications, nonunion or malunion, time to union, and length of inpatient hospital stay. Results: Ninety-five patients were included, with a mean age of 66 years; 57.9% of patients were female. The average body mass index was 30. Sixty-nine patients (72.6%) sustained a Weber B and 24 (27.4%) sustained a Weber C fracture. In addition, 26.3% were open fractures and all patients had soft tissue compromise affecting the lateral malleolus. The calculated infection rate for fibula nail was 4.2% and metalwork complication rate was 5.2%. The nonunion and malunion rate was 8.4% and rate of removal of hardware was 2.1%. The average time to union was 12.5 weeks, and length of inpatient stay was 9.4 days (SD 10). Conclusion: This multicenter study demonstrates that use of a fibula nail appears to be a safe approach to treating patients who have a physiologically higher risk of surgery, poor skin condition, and a complex fracture pattern. Level of Evidence: Level III, case-control study.